Patterns and Correlates of Self‐Management Strategies for Osteoarthritis‐Related Pain Among Older Non‐Hispanic Black and Non‐Hispanic White Adults. Issue 11 (24th September 2021) - Johnson, Alisa J.; Sibille, Kimberly T.; Cardoso, Josue; Terry, Ellen L.; Powell‐Roach, Keesha L.; Goodin, Burel; Staud, Roland; Redden, David; Fillingim, Roger B.; Booker, Staja Q.
Abstract : Objective: Knee osteoarthritis (OA) is a leading source of pain and disability among older adults. Self‐management (SM) strategies are recommended to manage OA symptoms. Sociodemographic and clinical characteristics, along with other factors, may influence SM utilization rate. This study sought to examine the prevalence and correlates of SM use for pain among non‐Hispanic Black patients (NHB) and non‐Hispanic White patients (NHW) older adults with or at risk for knee OA. Methods: A secondary data analysis was conducted on the Understanding Pain and Limitations in Osteoarthritic Disease multisite observational study, which included NHB (n = 104) and NHW (n = 98) community‐dwelling older adults with or at risk for knee OA. Participants completed measures of sociodemographics, pain SM use, coping, and clinical and experimental pain. Results: Clinical and experimental pain were significantly greater among NHBs compared to NHWs. There were no significant differences in use of total SM by ethnicity/race. Interestingly, multiple linear regression revealed that clinical and experimental pain indices, as well as coping, number of pain sites, age, and sex were differentially associated with total SM use between NHBs and NHWs. There were significant ethnicity/race by type of pain management interaction effects for pain measures. Conclusion: SM is common among older adults with or at risk for knee OA pain, and the prevalence of SM does not differ by ethnicity/race, but many guideline‐recommended interventions for OA are underutilized. Importantly, different factors were associated with the use of SM, highlighting distinct biopsychosocial mechanisms contributing to SM use in NHBs and NHWs.